2020
DOI: 10.21203/rs.3.rs-23643/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation of Gut Firmicutes/Bacteroidetes Ratio with Fibrosis and Steatosis in Patients with Non-alcoholic Fatty Liver Disease

Abstract: Background : We investigated the gut microbiota in patients with non-alcoholic fatty liver disease (NAFLD) and its correlation with fibrosis and steatosis as reflected in the controlled attenuation parameter and transient elastography valuesMethods : A cross-sectional study was performed on 37 patients with NAFLD at Cipto Mangunkusumo National General Hospital from December 2018 to March 2019. The gut microbiota was investigated in fecal samples with 16S RNA sequencing using the next-generation sequencing plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Therefore, the F/B ratio often serves as a marker of intestinal microbiome performance (Hildebrandt et al, 2009). Clinical studies found that the F/B ratio of NAFLD patients was positively correlated to steatosis (Jasirwan et al, 2021). The F/B ratio increased in HFD-induced NAFLD mice and decreased following bilberry anthocyanin intervention (Nakano et al, 2020), supporting the trend observed in this study.…”
Section: A B Csupporting
confidence: 84%
“…Therefore, the F/B ratio often serves as a marker of intestinal microbiome performance (Hildebrandt et al, 2009). Clinical studies found that the F/B ratio of NAFLD patients was positively correlated to steatosis (Jasirwan et al, 2021). The F/B ratio increased in HFD-induced NAFLD mice and decreased following bilberry anthocyanin intervention (Nakano et al, 2020), supporting the trend observed in this study.…”
Section: A B Csupporting
confidence: 84%
“…Furthermore, Proteobacteria are closely associated with hepatic and intestinal metabolism. For example, the abundance of Proteobacteria is positively correlated with nonalcoholic fatty liver fibrosis in the normal body mass index population (Jasirwan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown inconsistent and even contradictory results [29]. In the NAFLD patients, there is an increase in Bacteroidetes and Proteobacteria, although some studies found a reduction or no change in Bacteroidetes and correspondingly a decrease in Firmicutes [30]. An investigation in adults with NAFLD indicated a statistically significant relationship between the presence of steatohepatitis and an expanded level of Clostridium coccoides (Firmicutes phylum) and a decreased level of Bacteroidetes, which happened after adjusting BMI and dietary fat [31].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study indicated that among the bacteria detected in the blood of T2DM patients, 90% of the bacterial DNA belonged to the Gram-negative Proteobacteria phylum [42]. Recently, a study indicated that Proteobacteria was the only phylum strongly correlated with liver fibrosis in patients with normal BMI [30]. Based on numerous studies, there are only four major phyla in the human intestinal microbiome that 90% of them are Gram-positive Firmicutes and Gram-negative Bacteroidetes, that Actinobacteria and Proteobacteria represent the remaining 10%.…”
Section: Discussionmentioning
confidence: 99%